2020
DOI: 10.1016/j.carbpol.2020.116918
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose-lignin composite fibers as precursors for carbon fibers: Part 2 – The impact of precursor properties on carbon fibers

Abstract: Cellulose-lignin composite fibres as precursors for carbon fibres. Part 2 -The impact of precursor properties on carbon fibres Nguyen-Duc Le (Conceptualization) (Investigation) (Formal analysis) (Writing -original draft) (Visualization), Mikaela Trogen (Resources) (Investigation) (Writing -review and editing), Yibo Ma (Investigation) (Writing -review and editing), Russell J. Varley (Supervision) (Writing -review and editing), Michael Hummel (Conceptualization) (Writing -review and editing) (Funding acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 33 publications
3
50
1
Order By: Relevance
“…xylan, can be dissolve in ILs at moderate concentrations (Roselli 2017), but it is expected that they precipitate in the coagulation bath during spinning. Meanwhile, a certain amount of lignin can be utilized during the spinning process if carbon fibers are desired (Le et al 2020;Ma et al 2015). Beside impurities, one can expect minor losses in the degree of polymerization (DP) of cellulose over the dissolution and regeneration stages (Parviainen et al 2015).…”
Section: Impurities and Side-products In Ioncellmentioning
confidence: 99%
“…xylan, can be dissolve in ILs at moderate concentrations (Roselli 2017), but it is expected that they precipitate in the coagulation bath during spinning. Meanwhile, a certain amount of lignin can be utilized during the spinning process if carbon fibers are desired (Le et al 2020;Ma et al 2015). Beside impurities, one can expect minor losses in the degree of polymerization (DP) of cellulose over the dissolution and regeneration stages (Parviainen et al 2015).…”
Section: Impurities and Side-products In Ioncellmentioning
confidence: 99%
“…The effects of processing parameters (i.e., draw ratio, stabilization/carbonization temperature, lignin content, etc.) on the structure and mechanical properties of lignin/cellulose precursor fibers and carbon fibers have been investigated systematically [ 139 , 155 , 156 , 157 ], from which it is concluded that the cellulose constituent dominates precursor fiber structure and mechanical performance. Increasing lignin content decreases fiber strength due to the disturbance of oriented cellulose crystallites [ 141 , 158 , 159 ] and increases carbon yield [ 160 ] due to lignin’s carbon-rich structure.…”
Section: Mechanical Performance Of Lignin-based Fibersmentioning
confidence: 99%
“…Using the Ioncell Ò technology (Sixta et al 2015), we are able to dissolve mixtures of biopolymers in a protic ionic liquid and spin the solution into hybrid fibers. The obtained hybrid fibers are composed of two or more biopolymers forming nanoscale mixtures inside a micrometric fibrous matrix (Mikkilä et al 2020;Zahra et al 2020;Le et al 2020;Trogen et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid fibers like cellulose-lignin (Bengtsson et al 2019;Mikkilä et al 2020;Le et al 2020;Trogen et al 2021), cellulose-chitosan (Zahra et al 2020), cellulose-chitin (Ota et al 2020) or cellulose-betulin (Makarov et al 2018) have found applications in textiles (Ma et al 2015) or as precursors for biobased carbon fibers (Byrne et al 2016). The presence of a second biopolymer provides to the hybrid fiber new functional properties that can be fine-tuned by controlling the share of the biopolymer in the fiber.…”
Section: Introductionmentioning
confidence: 99%